A2.37 B cells regulate follicular helper T cells in healthy individuals and sjögren's patients but are defective in SLE patients. (24th February 2016) - Achour, A; Pers, JO; Youinou, P; Hillion, S; Jamin, C
Abstract : Background and objectives: Follicular helper T (Tfh) cells are instrumental in the development of humoral responses, bringing helper signals to B cells for their terminal differentiation. Abnormal functions are deleterious and can trigger autoimmunity. Regulatory B (Breg) cells are known to modulate Th1 polarisation. Their control on humoral response has been hardly evaluated. The aim of our work was to establish the capacity of Breg cells to modulate the Tfh-dependent humoral response in healthy conditions and to determine their efficiency in Sjögren and SLE patients. Materials and methods: Peripheral blood T and B cells were purified from healthy indviduals and from Sjögren and SLE patients. The polarisation of human T cells into Tfh cells was obtained using stimulation with anti-CD3 + anti-CD28 Abs in association with a cocktail of IL-12+IL-21. The functional activities of Tfh-differentiated cells were evaluated in co-cultures at a 1:1 ratio measuring the differentiation of B cells into memory B cells and plasma cells by flow cytometry, and the Ig productions in the supernatants by ELISA. The control of Breg cells on Tfh-dependent humoral responses was determined using 1:1:1 co-culture experiments with Tfh-differentiated cells, B cells and Breg cells. Results: In 1:1 co-culture experiments, Tfh-differentiated cells from healthy donors induced the maturation of naive B cells into IgD-CD27 + memory B cells and CD138 + plasma cells, and triggered the secretion of IgM, IgG and IgA. In 1:1:1 co-culture conditions, Breg cells restrained the expression of Bcl-6, IL-21, ICOS, CXCR5 and PD-1 on T cells, all characteristics of Tfh cell polarisation. Furthermore, they inhibited the Tfh-dependent induction of CD138 + plasma cells and of IgD-CD27 + memory B cells, and down-regulated the secretion of Igs. Interestingly, we demonstrated that SLE Breg cells were defective in regulating the Tfh cell polarisation as well as the Tfh-dependent B cell responses. In contrast, Sjögren Breg cells were highly efficient. Conclusions: Our results suggest that Breg cells from healthy individuals can control the Tfh-dependent humoral response. Moreover, this control appears efficient in Sjögren's patients but deficient in SLE patients. Overall, these data suggest differential impairment of the autoimmune humoral responses in SLE and Sjögren patients.